Edukasi Kesehatan dalam Upaya Menurunkan Kejadian Stroke Berulang pada Pasien Hipertensi - Prayoga, Dimas Hadi; Twistiandayani, Retno; Manan, Abdul; Wijayati, Lilik (STIKES Yayasan RS.Dr.Soetomo, 2024)
Introduction: Hypertension is a disease that initiates various degenerative diseases which is generally a condition without symptoms, where high blood pressure in the arteries can cause the risk of developing cardiovascular-related diseases such as stroke, kidney failure, heart attack and kidney damage. To increase patient understanding in carrying out independent care at home, health education is needed that discusses caring for stroke patients at home. The aim of this community service is to provide health education to increase patient knowledge in an effort to reduce the incidence of recurrent stroke. Method: The method used in this community service is to provide intervention in the form of health education. Evaluation of community service uses pre-test and post-test knowledge methods. Number of participants 20 people Results: This community service is related to providing education to increasing knowledge of stroke patients. . Conclusion: The application of education can be carried out as a preventive and promotive effort for stroke patients so that patients can carry out treatment independently at home and reduce the incidence of recurrent strokes